Solve: Testing the interrelationships among employees in medium scale enterprises (2011)
The study examined interrelationships of emerging psychosocial problems (stress, tobacco and alcohol use, HIV/AIDS, and violence, as addressed by ILO's SOLVE program) in medium scale enterprises. They constitute major challenges to employees’ health and organizational outcomes. Unlike other countries, where strong evidence exists to show the interrelationships, there is paucity of literature involving the Sub-Saharan Africa sample, where attempts to promote the knowledge and application of SOLVE has posed great problems. Based on previous literature, it was hypothesized that there would be significant positive interrelationships among the dimensions in SOLVE. The survey utilized a questionnaire, consisting of 20 items, measuring the dimensions in SOLVE. A sample of 186 respondents was drawn from middle-level supervisors in medium scale enterprises. They are students in a weekend Master’s in Managerial Psychology (MMP) program. There were 102 (54.8%) male and 84 (45.2%) female respondents. Their mean age was 36 (sd=3.55). Findings established significant interrelationships among the five psychosocial factors, i.e. SOLVE dimensions, which confirmed the hypothesis. There was no significant difference between males and females in their responses to the measures. Apart from adding to previous literature on the association of the variables, the outcome will enable the promotion of SOLVE among workers as a best practice in creating healthy workplaces